1991
DOI: 10.1128/jvi.65.11.6252-6259.1991
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Epstein-Barr virus BamHI A fragment in nasopharyngeal carcinoma: evidence for a viral protein expressed in vivo

Abstract: A family of mRNAs that are transcribed rightward through the BamHI A fragment have been detected in C15, a nasopharyngeal carcinoma (NPC) which has been passaged in nude mice. Northern (RNA) blot hybridizations indicate that these RNAs are also expressed in three other NPCs which have been established in nude mice and in an NPC obtained at biopsy. Moreover, hybridization in situ detected transcription from BamHI A in 12 NPCs and 1 Epstein-Barr virus (EBV)-containing carcinoma of the parotid gland. In each case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…The identification of novel latent transcripts running through the BamHI A region of the EBV genome in the opposite orientation to conventional BamHI A transcripts of the virus lytic cycle came from work on a nude mousepassaged NPC cell line C15 (18,19). Such "rightwardrunning" transcripts appear, from limited analyses published to date, to be a consistent feature of NPC (53). Using PCR primers spanning introns in the largest BamHI A-specific cDNA isolated from the C15 NPC line, we have recently detected transcripts with this splice structure in 10 fresh NPC biopsies (Brooks et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of novel latent transcripts running through the BamHI A region of the EBV genome in the opposite orientation to conventional BamHI A transcripts of the virus lytic cycle came from work on a nude mousepassaged NPC cell line C15 (18,19). Such "rightwardrunning" transcripts appear, from limited analyses published to date, to be a consistent feature of NPC (53). Using PCR primers spanning introns in the largest BamHI A-specific cDNA isolated from the C15 NPC line, we have recently detected transcripts with this splice structure in 10 fresh NPC biopsies (Brooks et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Given the similarities between NPC and HD with regard to EBV gene expression, we analyzed EBV-positive HD cases for such mRNAs and found easily detectable expression of the appropriately spliced transcript in all but one case. While a putative BamHI A-encoded protein product has been identified (53), the lack of a suitable antibody reagent precludes analysis of the expression of this protein in biopsies of NPC and HD. Whatever the function of the protein encoded by the BamHI A transcript, the expression of this mRNA in EBVpositive HD dearly indicates that it is not preferentially expressed in epithelial cells as has previously been suggested (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of viral polymorphism showed no significant difference between young and adult North African NPC patients [Bouzid et al, 19941, but only some 50% of young patients possessed IgA antibodies to viral capsid antigens (VCA) antigens despite a vigorous I g G response [Bouguermouh, 19851. EBV infection of NPC biopsy specimens may be of either the productive (lytic) or latent type [Raab-Traub et al, 19831, and genes. Transcription of BARF0 has been studied extensively by Northern hybridization [Gilligan et al, 1991;Chen et al, 1992;Karran et al, 19921, but that of other genes such as LMP1, LMP2, EBNA1, EBERs and BLZFl has only been demonstrated in NPC biopsies by reverse transcriptase-polymerase chain reaction (RT-PCR) [Brooks et al, 1992;Busson et al, 19921 or in situ hybridization ICochet et al, 1993;Wu et al, 19911. Viral peptides involved in latent infection, such as EBNAl and LMP1, are expressed by a variable number of cells in NPC biopsies [Fahraeus et al, 1988;Young et al, 19881, and early proteins such as ribonucleotide reductase, EA-D (BMRFl), EA-R (BHRFI) and BZLFl have been detected using monoclonal antibodies [Luka et al, 1988;Lung et al, 1989;Cochet et al, 19931.…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam has one of the highest incidence rates of NPC in worldwide 1,2 . According to statistics of Globocan (2012), the high prevalence of NPC cases was observed the member of the BamHI-A Rightward Transcripts (BARTs) family, RPMS1 expression has been confirmed in all EBV-associated tumors [9][10][11][12][13] . A number of studies have reported attempts to identify the NPC associated EBV genes' variations, including EBV Nuclear Antigens (EBNAs), Latent Membrane Proteins (LMPs) and EBVencoded small nuclear RNAs (EBERs), have been shown to be associated with NPC pathogenesis [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%